Model of a wind turbine using discrete events. (January 2019) - Garcia, Stefany; Herrera, Jorge; Aristizábal, Andrés Julián; Castañeda, Mónica; Zapata, Sebastian; Pelaez-Restrepo, Julián
Abstract: This paper presents the model of a wind turbine using SimEvents, the discrete-event simulator from Matlab. The advantage of this proposal is that different wind profiles can be generated by using the time series representing the wind dynamics. The adequate functioning of the model is corroborated using the k and c parameters of Weibull distribution. As a result, the power profiles for the years 2000 to 2013 are obtained. Such simulator allows to find the wind potential when knowing the time series of the wind speeds.